Long non-coding RNA JPX promotes endometrial carcinoma progression via janus kinase 2/signal transducer and activator of transcription 3 - Xiong, Hanzhen; Zhang, Wei; Xie, Mingyu; Chen, Ruichao; Chen, Hui; Lin, Qiongyan (Frontiers in Oncology, 2024)
Although LncRNA JPX has been linked to a number of malignancies, it is yet unknown how it relates to endometrial carcinoma (EC). Investigating the expression, functional activities, and underlying molecular processes of lncRNA JPX in EC was the goal of this work. RT-qPCR was used to examine the differences in lncRNA/microRNA (miRNA, miR)/mRNA expression between normal cervical and EC tissues or cells. Cell Counting Kit-8, flow cytometry, and transwell were used to evaluate the association between lncRNA JPX/miR-140-3p/phosphoinositide-3-kinase catalytic subunit α (PIK3CA) in Ishikawa and JEC cell lines. The impact of JPX on the downstream janus kinase (JAK)2/signal transducer and activator of transcription (STAT)3 signaling pathway was investigated using Western blot analysis. When comparing EC tissues to nearby normal tissues, JPX expression is markedly increased in EC tissues, with greater expression in advanced-stage EC.Furthermore, compared to normal epithelial cells, EC cell lines have higher levels of JPX expression.In Ishikawa and JEC endometrial cancer cell lines, we used siRNA-mediated suppression of JPX to find lower cell viability, increased apoptosis, cell cycle arrest, and reduced migration and invasion.We next verified that miR-140-3p binds to downstream target cells to impede the transcription and translation of PIK3CA, which in turn prevents the growth of Ishikawa and JEC cells. JPX functions as a ceRNA to adsorb miR-140-3p. This procedure required controlling JAK2/STAT3, a downstream signal. In summary, JPX enhances the development of Ishikawa and JEC cells and activates downstream JAK2/STAT3 signal transduction via the miR-140-3p/PIK3CA axis, offering a possible therapeutic target for the treatment of EC.